Penerapan Prinsip Green Chemistry Dalam Penggantian Styrofoam dengan Material Ramah Lingkungan - Abdaniah, Cahayu; Nursyifa, Elena; Yuniarti S, Fitri; Susilawati, Kasih (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2024)
Green chemistry principles have an important role in reducing Styrofoam waste. Styrofoam waste is generated everywhere, especially in school environments. styrofoam is packaging that is effective and practical to use, however, there are dangerous contents that can cause serious illnesses from styrofoam. There is a need to replace styrofoam with environmentally friendly containers such as food containers that can be used repeatedly. The purpose of this research is to measure the level of students' understanding and application of green chemistry principles in the SMAN Jatinunggal school environment. The research method used in this research is a questionnaire-based quantitative descriptive approach distributed online to students at SMAN Jatinunggal. The number of respondents was 17 grade 12 students at SMAN Jatinunggal. From the research results, it can be concluded that the level of understanding of grade 12 students at SMAN Jatinunggal regarding the meaning and understanding of the principles of green chemistry is quite adequate. However, in its application the application of green chemistry principles at SMAN Jatinunggal school has not been optimal. This is caused by a lack of advice from the school so that many traders still use styrofoam which is a factor in the accumulation of styrofoam waste in the school environment